Power sharing at the local level: Evidence on opting-in for non-citizen voting rights - Michaela Slotwinski; Alois Stutzer (University of Basel, Center of Business and Economics (WWZ), 2019)
The enfranchisement of foreigners is likely one of the most controversial frontiers of institutional change in developed democracies, which are experiencing an increasing number of non-citizen residents. We study the conditions under which citizens are willing to share power. To this end, we exploit the unique setting of the Swiss canton of Grisons, where municipalities are free to decide on the introduction of non-citizen voting rights at the local level (a so called opting-in regime). Consistent with the power dilution hypothesis, we find that enfranchisement is less likely the larger the share of resident foreigners. Moreover, municipalities with a large language/cultural minority are less likely to formally involve foreigners. In contrast, municipality mergers seem to act as an institutional catalyst, promoting democratic reforms. A supplementary panel analysis on electoral support for an opting-in regime in the canton of Zurich also backs the power dilution hypothesis, showing that a larger share of foreigners reduces support for a regime change.
Keywords: D72; D78; J15; K16; 330; non-citizen voting rights; opting-in; power sharing; democratization